Current Update on the Risk Factor Modification and Excercise Following Coronary Artery Disease - Nia Dyah Rahmianti; Teuku Yusrizal; Makhyan Jibril Al-Farabi (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Coronary artery disease (CAD) becomes primary disease causing morbidity and mortality in developed country. Chronic CAD disease progress over years or decades and becomes a significant health burden worldwide. Most CAD cases occur in individuals with at least one risk factor. Thus, risk modification and regular exercise are part of coronary artery disease management to reduce disease progression. Regular exercise training is an intense technique to expand the threshold of angina-free activity levels in stable disease conditions when symptomatic CAD has developed. This review will explain the current updates in the risk management and exercise that can be used to improve patients’ quality of life and reduce the severity progression of the disease.